PENGARUH PENGGUNAAN APE GEOROBOT TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA 5-6 TAHUN DI PAUD AQEELA KECAMATAN TAMPAN KOTA PEKANBARU - Gessi Firdawati; Devi Risma; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observations on the ability to recognize the shape of the geometry of students has not developed optimally. So it is necessary to apply the georobot educational game. The purpose of this study was to examine the effect of using georobot educational game on the ability to recognize geometric shapes of children aged 5-6 years. This research was conducted at PAUD Aqeela Tampan District of Pekanbaru City during September 2018. The research used experimental method with one group pre-test post-test design with 15 samples. The data collection technique used in this research is using observation sheet the ability to recognize the shape of the geometry. Data anlisis technique using t-test by using SPSS program ver 20. From result of data analysis obtained tcount equal to 38,241 bigger than t table = 2,145 with sig 0.000 <0.05. It can be concluded that there are differences in the ability to recognize geometric shapes significantly before and after the application of the georobot educational game. Based on hypothesis test results obtained there is the effect of use georobot educational game to the ability to recognize the geometry of children aged 5-6 years in PAUD Aqeela Tampan District of Pekanbaru City of 62,24%.Keywords: Geometric Shape, Georobot Educational Game.